Implementasi Media Genially dalam Pembelajaran Bahasa Indonesia Bagi Mahasiswa PBSI UIN Jakarta - Siti Rinjani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This research describes the Genially learning media for learning Indonesian for 5th semester students at PBSI UIN Jakarta. This research uses a qualitative descriptive method. The objects in this research were PBSI semester 5 students with a total of 32 students as respondents. The data collection techniques used in this research are observation, documentation and questionnaires. These three techniques can include direct observation, document analysis and direct responses from respondents. Based on the research results and responses from PBSI 5th semester students regarding the use of Genially learning media, it can be concluded that the majority of respondents consider technology-based learning media such as Genially to be effective in increasing students' enthusiasm for learning. The success of learning media is assessed by its attractiveness, usefulness, and ease of access and use. Thus, it can be concluded that Genially is considered an effective and interesting learning media for PBSI 5th semester students. This positive reception can become the basis for further development in improving the quality of technology-based learning in the future.